Earthquake resistant engineering structures VIII - International Conference on Earthquake Resistant Engineering Structures 2011 : Chianciano Terme, Italy); Brebbia, C. A.; Maugeri, Michele; Wessex Institute of Technology (Billerica, MA : Computational Mechanics Inc., 2011)
Based on the proceedings of the Eighth International Conference on Earthquake Resistant Engineering Structures (ERES), this book presents basic and applied research in the main fields of engineering relevant to earthquake resistant analysis and design of structural systems.
'Organised by Wessex Institute of Technology, UK'--Prelim.
Includes bibliographical references and index.
Keywords: Earthquake engineering -- Congresses; Earthquake resistant design -- Congresses